Understanding physical activity participation among underserved women: a mixed-methods cross sectional study using an ecological framework - Jude Ominyi; Andrew Clifton; Aaron Nwedu (BMC Public Health)
Abstract Background Physical inactivity remains a major contributor to non-communicable diseases and health inequalities in the UK, particularly among underserved women living in socioeconomically deprived areas. In post-industrial port communities across Suffolk and Norfolk such as Ipswich, Lowestoft, Great Yarmouth, and Felixstowe, women face intersecting barriers to physical activity (PA), including gender norms, ethnicity, chronic illness, caregiving duties, and limited access to affordable, culturally appropriate PA opportunities. This study addresses a critical evidence gap by exploring multi-level influences on PA engagement among these populations using an ecological and intersectional lens. Methods A convergent parallel mixed-methods design was employed, guided by Bronfenbrenner’s Ecological Systems Theory. Quantitative data were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) and the Exercise Benefits and Barriers Scale (EBBS), administered to 112 women aged 18–65 recruited from community-based PA and weight-loss programmes. Embedded within the survey were open-ended prompts capturing lived experiences. Data were analysed using SPSS v29 for t-tests, chi-square tests, and logistic regression, while qualitative data underwent thematic analysis using NVivo 14. Findings were integrated across five ecological levels: microsystem, mesosystem, exosystem, macrosystem, and chronosystem. Results Only 58% of participants met recommended PA guidelines. Key barriers included chronic health conditions (Odds Ratio (OR) = 0.50), caregiving responsibilities (OR = 0.56), low self-confidence (OR = 0.49), and cost (OR = 0.59). Qualitative findings revealed intersecting challenges, such as cultural expectations, modesty norms, family criticism, lack of safe infrastructure, and inconsistent PA programme availability. Divergences between high EBBS benefit scores and narratives of demotivation highlighted emotional dissonance and structural constraints. Temporal factors like motherhood, menopause, and community service cuts also disrupted sustained engagement. Conclusion Women’s PA behaviours in these areas are shaped by a complex interplay of individual, social, structural, cultural, and temporal factors. One-size-fits-all behavioural messaging is insufficient. Effective interventions must be inclusive, culturally sensitive, and rooted in local realities. This study offers a robust foundation for designing equity-focused, multi-level strategies to promote PA in underserved communities.